A história local na perspectiva da cidadania planetária: a experiência em uma disciplina eletiva da EEMTI Francisco Jaguaribe em Jaguaruana-CE - Sampaio, Perpétua Socorro Lopes (2023)
This study focuses on an elective curriculum component (Local History) belonging to the curriculum of a full-time school located in the state of Ceará in the municipality of Jaguaruana. It is part of the project Planetary Citizenship in the Brazilian university curriculum, developed by the Curriculum group of the Federal University of Ceará. Planetary Citizenship is understood as the radical defense of all forms of life on the planet, including indigenous peoples and afrodescendants, with their knowledge and traditions, together with the knowledge built by scientists in their laboratories, universities and research institutions. While Local History portrays the historicity of the subjects from their local context, Planetary Citizenship broadens the approach by relating Local History to the Planet, seen not only from the economic, political, cultural side, but also in relation to ancestry, spirituality, affectivity, and our relationship with the natural environment. The research aimed to reflect among the students of the first years about the importance of studying the elective subject Local History, included in the curricular proposal of the new high school in the state of Ceará, in dialogue with Planetary Citizenship. In methodological terms, the study was qualitative in nature and the procedures were based on documentary and field research. In the document analysis, we examined the Political Pedagogical Project of the school that was the locus of our research. The field research, in the participatory research modality, aimed to understand the possibilities of developing, in the Local History Elective (curricular component), studies directed to daily practices, to political, economic and cultural knowledge, based on the idea of planetary citizens. The experience of the participant research process led us to the verification of how important it is the insertion of the study of Local History in the school space, contributing to the awakening, in the students, of planetary consciousness, the basis of Planetary Citizenship.